Writing Home: Representations of the Native Place in Modern Japanese Literature - Dodd, Stephen, 1955- (Book collections on Project MUSE., 2004)
"This book examines the development of Japanese literature depicting the native place, or furusato, from the mid-Meiji period through the late 1930s as a way of articulating the uprootedness and sense of loss many experienced as Japan modernized. The 1890s witnessed the appearance of fictional works describing a city-dweller who returns to his native place, where he reflects on the evils of urban life and the idyllic past of his childhood home. The book concentrates on four authors who made use of this trend: Kunikida Doppo, Shimazaki Toson, Sato Haruo, and Shiga Naoya."--Jacket.